I assume that the first equation is actually y=-3x+2. Using substitution, you can use either x or y from one equation and substitute it into the other equation. I highly suggest using x in x-y=2. To find what x is equal to, move -y to the other side of the equal sign by adding y to both sides so that you have: x=y+2 Now, you have what x is equal to, which would be y+2. Substitute y+2 into the equation y=-3x+2, in place of the x. y=-3(y+2)+2 y=-3y-6+2 y=-3y-4 y+3y=y-3y+3y-4 4y=-4 y=-1 Now, you have what y is equal to. To further solve for x, substitute what you got for y into the either one of the equations. I usually just use the other equation, it's not so confusing for me that way. You can solve it this way; x=-1+2 x=1 or you can solve it in this way... x-(-1)=2 x+1=2 x=1 Here are your final answers: x=1 and y=-1. Hope this helps :-)

(1) Answers

Add answer

Sign in
Sign up